A disaggregated and macro-consistent Social Accounting Matrix for Pakistan - Debowicz, Darío; Dorosh, Paul A.; Haider, Hamza S.; Robinson, Sherman (Springer, 2013)
This paper provides future researchers of economic structure with a model for building a social accounting matrix (SAM), that is, a unique countrywide database for use in structural analysis, and applies this model to the empirical investigation of the economic structure of Pakistan. Our proposed approach to building SAMs is motivated by an information theoretic approach to estimation that takes a Bayesian view of the efficient use of information: "Use all the information you have, but do not assume any information you do not have." The methodology used to develop this SAM, unlike previous approaches, ensures that it is perfectly consistent with the national accounts. The SAM provides a high degree of detail on the economic structure of the country, with 51 sectors of activity, 27 factors of production, and 18 household groups, allowing the tracing of direct and indirect effects of potential scenarios through production and consumption linkages and the capture of distributional effects. Output multipliers in Pakistan, accounting for supply constraints, range from 1.1 to 1.4, and shocks to livestock and industry have the largest spillover effects. These shocks lead to income changes that differ significantly across domestic socioeconomic groups, a direct result of the heterogeneity in the generation of income of these groups that our countrywide database captures. JEL Classification:E160, E170.